Semiconducting alternating multi-block copolymers via a di-functionalized macromonomer approach. Issue 5 (3rd January 2017) - Gasperini, A.; Johnson, M.; Jeanbourquin, X.; Yao, L.; Rahmanudin, A.; Guijarro, N.; Sivula, K.
Abstract : A route to fully-conjugated semiconducting block copolymers is presented and the prototype exhibits nanoscopic phase domain separation and good mobility. Abstract : The development of fully-conjugated semiconducting block-copolymers is an important goal for organic electronics, but to date has been almost exclusively limited to materials containing poly(3-alkylthiophenes). Here we present the prototype of a class of fully-conjugated semiconducting block copolymers (prepared using a versatile route based on conjugated macromonomers and a cross-coupling polycondensation) that exhibit hole mobility in field effect transistors of the order of 0.1 cm 2 V −1 s −1 and nanoscopic phase domain separation.